2015
DOI: 10.1124/jpet.115.228411
|View full text |Cite|
|
Sign up to set email alerts
|

  Adrenergic Receptor Kinase C-Terminal Peptide Gene-Therapy Improves  2-Adrenergic Receptor-Dependent Neoangiogenesis after Hindlimb Ischemia

Abstract: After hindlimb ischemia (HI), increased catecholamine levels within the ischemic muscle can cause dysregulation of b 2 -adrenergic receptor (b 2 AR) signaling, leading to reduced revascularization. Indeed, in vivo b 2 AR overexpression via gene therapy enhances angiogenesis in a rat model of HI. G proteincoupled receptor kinase 2 (GRK2) is a key regulator of bAR signaling, and b adrenergic receptor kinase C-terminal peptide (bARKct), a peptide inhibitor of GRK2, has been shown to prevent bAR down-regulation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Importantly, the activation of such signaling pathway leads to the reciprocal downregulation of β 1 AR and S1PR 1 in cardiac myocytes, leading to worse remodeling and progression toward HF ( Cannavo et al, 2013b ). This study further supported the idea that blockade of GRK2 is a valid strategy to prevent HF development and progression, but also demonstrated the cardioprotective role of S1PR 1 ( Cannavo et al, 2013a , 2016a , b ; Cannavo and Koch, 2017a ). In line with these data, we recently reported that activation of S1PR 1 in the heart is also modulated by the β 3 AR ( Cannavo et al, 2017 ).…”
Section: S1p Receptors and Dependent Signaling In Cardiovascular Systsupporting
confidence: 82%
“…Importantly, the activation of such signaling pathway leads to the reciprocal downregulation of β 1 AR and S1PR 1 in cardiac myocytes, leading to worse remodeling and progression toward HF ( Cannavo et al, 2013b ). This study further supported the idea that blockade of GRK2 is a valid strategy to prevent HF development and progression, but also demonstrated the cardioprotective role of S1PR 1 ( Cannavo et al, 2013a , 2016a , b ; Cannavo and Koch, 2017a ). In line with these data, we recently reported that activation of S1PR 1 in the heart is also modulated by the β 3 AR ( Cannavo et al, 2017 ).…”
Section: S1p Receptors and Dependent Signaling In Cardiovascular Systsupporting
confidence: 82%
“…Cell migration was assessed by wound-healing scratch assay as previously described 59 . After isolation, cardiac fibroblasts (∼3 × 10 5 ) were plated in 12-well tissue culture plates.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, activation of Akt and eNOS, and the consequent secretion of NO, has been proven to directly stimulate endothelial cell function and promote the neoangiogenesis. 50 Further, as discussed above, the eNOS-mediated generation of NO is also responsible for cGMP and PKG activation, thus directly conferring beneficial effects on the myocardium. 51 …”
Section: Introductionmentioning
confidence: 96%
“… 56 , 57 Of note, enhancement of neoangiogenesis in the failing heart is considered one of the mechanisms of protection activated by this class of drugs. 58 In this context, nebivolol through β 3 AR activation increases the generation of NO, a key mediator of endothelial function, 50 enhancing endothelial proliferation and increasing vasodilation. 56 , 57 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation